Initial Reports of the Deep Sea Drilling Project 1985
DOI: 10.2973/dsdp.proc.85.115.1985
|View full text |Cite
|
Sign up to set email alerts
|

Calcareous Nannofossil Biostratigraphy, Deep Sea Drilling Project Leg 85, Eastern Equatorial Pacific

Abstract: Pelagic sediments recovered during Leg 85 span the uppermost Eocene to Pleistocene interval in a series of fairly continuous sections. The calcareous nannofossils are normally not very well preserved in the cores from this leg; coccoliths, discoasters, and other morphologic types have been corroded and overgrown by secondary calcite. Poor preservation in some cases precludes a sharp and precise biostratigraphy at the subzonal level, although remarkably, most zones can be clearly identified. Middle Miocene mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…We monitored the range of Discoaster kugleri with an attempt to clarify the biostratigraphic value of the species, which is a wellknown "controversial" marker in the middle Miocene interval. The FO of the species, which defines the boundary CN5a/CN5b (Bukry, 1973), is considered a weak marker by many authors (e.g., Gartner and Chow, 1985;Fornaciari et al, 1990). Gartner (1992) The species, indeed, is a "sporadic, tropical species" (Bukry, 1973, p. 692), but it seemed the only criterion for dividing Zone CN5, which spans a time interval of about 3.0 m.y.…”
Section: Fo Of Calcidiscus Macintyrei (9)mentioning
confidence: 99%
“…We monitored the range of Discoaster kugleri with an attempt to clarify the biostratigraphic value of the species, which is a wellknown "controversial" marker in the middle Miocene interval. The FO of the species, which defines the boundary CN5a/CN5b (Bukry, 1973), is considered a weak marker by many authors (e.g., Gartner and Chow, 1985;Fornaciari et al, 1990). Gartner (1992) The species, indeed, is a "sporadic, tropical species" (Bukry, 1973, p. 692), but it seemed the only criterion for dividing Zone CN5, which spans a time interval of about 3.0 m.y.…”
Section: Fo Of Calcidiscus Macintyrei (9)mentioning
confidence: 99%
“…This event is considered as poor by many authors (e.g. Gartner and Chow, 1985), and alternative criteria have been proposed to recognize this boundary. Bukry (1973) proposed the LO of Cyclicargolithus floridanus as a secondary marker for the base of CN5b Subzone.…”
Section: Cn5b Subzone and Nn7 Zonementioning
confidence: 99%
“…Ellis (1981) suggested as a substitute event the FO of Discoaster bollii. Gartner and Chow (1985) suggested that the LO of Coronocyclas nitescens may be useful in subdividing the interval above the LO of Sphenolithus heteromorphus and below the FO of C. coalitus.…”
Section: Cn5b Subzone and Nn7 Zonementioning
confidence: 99%
“…This event is difficult to establish precisely because of taxonomic difficulties involving the presence of atypical specimens, most probably related to Discoaster musicus, and because of the discontinuous distribution of D. kugleri. The FO of D. kugleri is considered as a less reliable biostratigraphic indication also in previous studies (i.e., Gartner and Chow, 1985), and alternative criteria have been proposed to subdivide the CN5 (NN6/NN7) zonal interval: the LO of Cyclicargolithus floridanus (Bukry, 1973), the FO of Discoaster bollii (Ellis, 1981), and the LO of Coronocyclus nitescens (Gartner and Chow, 1985). Of these three events, the LO of C. floridanus is discussed above.…”
Section: The Subdivision Of Middle Miocene Zone Cn5mentioning
confidence: 99%